Cloudy day/sunny day - Crews, Donald (Orlando : Green Light Readers/Harcourt, 2003)
Whether the day is cloudy or sunny, it provides lots of opportunities for fun and entertainment.
First Green Light Readers edition 1999.
Ages 4-6; grade 1.
Keywords: Play -- Fiction; Weather -- Fiction